Analisis Kemandirian Keuangan Daerah dalam Pengelolaan Keuangan pada Pemerintah Provinsi Bengkulu - Efriyanto, Rozi; Herawati, Helmi; Sari, Nina Yuliana (https://jurnal.binamandiri.ac.id/, 2023)
Financial independence is one indicator of the success of regional autonomy. This study aims to analyze and determine regional financial independence in financial management at the Bengkulu Provincial Government. The type of data used in research is quantitative data. The sample of this research is the regional financial reports of Bengkulu Province from 2017 to 2021. The analytical method used is descriptive research. The results of the study show that the average ratio of the level of independence in Cities and Regencies in Bengkulu Province from 2017 to 2021 is 6.88% at the level of instructive relationship patterns. The average level of regional financial capacity of Cities and Regencies in Bengkulu Province during the 2017-2021 fiscal year period is 100.48% so it is classified as having very good regional financial capacity because this figure is at intervals > 50%. If seen from the average value, it can be seen that the effectiveness ratio of the Cities and Regencies of Bengkulu Province from 2017 to 2021 is 87.91% with a quite effective relationship pattern because it is in the 80-90 interval. The efficiency ratio for the 2017 to 2021 fiscal years is an average of 1,841.87% which reflects inefficient financial performance due to the fact that the total regional expenditure costs are greater than the realization of PAD.